2016
DOI: 10.1515/ntrev-2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

Water inside carbon nanotubes: structure and dynamics

Abstract: Studying the properties of water confined in carbon nanotubes (CNTs) have gained a lot of interest in recent years due to the vast potential applications of systems in nanoscale liquid transport as well as biology functions. This article presents a comprehensive review of recent experimental and theoretical results using nuclear magnetic resonance (NMR) and molecular dynamics (MD) simulations. Different NMR methods including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 112 publications
3
72
0
Order By: Relevance
“…Functional groups activated through atmospheric-pressure plasma treatment increase the formation of hydrophilic groups on the surface of the CNTs and are directly related to the increase in surface free energy. On the other hand, oxygen treatments have the advantage of increasing the interfacial adhesion and wetting properties of the fiber while attaching various functional groups such as carboxyl (-COOH), carbonyl (-CO), and hydroxyl groups (-OH) [37,38]. This can be interpreted as a method to enable better interfacial adhesion and interactions between the CNTs and the epoxy matrix of multi-scale composites, providing excellent mechanical properties [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Functional groups activated through atmospheric-pressure plasma treatment increase the formation of hydrophilic groups on the surface of the CNTs and are directly related to the increase in surface free energy. On the other hand, oxygen treatments have the advantage of increasing the interfacial adhesion and wetting properties of the fiber while attaching various functional groups such as carboxyl (-COOH), carbonyl (-CO), and hydroxyl groups (-OH) [37,38]. This can be interpreted as a method to enable better interfacial adhesion and interactions between the CNTs and the epoxy matrix of multi-scale composites, providing excellent mechanical properties [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…[2,31,32] Besides, experimental results are controversial and open problems remain. [33] This is the main reason why there has been a greater interest in using theoretical approaches or molecular simulations to un-derstand, for instance, the effect of varying the geometrical parameters defining the nano confinement and/or the thermodynamic conditions. [24,[34][35][36][37][38][39][40][41] However, to our knowledge, neither the theoretical and simulations approaches, nor the experimental ones, have so far reached a consensus on how water transport properties are affected under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[24,[34][35][36][37][38][39][40][41] However, to our knowledge, neither the theoretical and simulations approaches, nor the experimental ones, have so far reached a consensus on how water transport properties are affected under these conditions. [33,42] Thus, molecular dynamics (MD) simulation is a very important tool to study confined water. A good force field is then required to model the water-water and the water-wall interactions.…”
Section: Introductionmentioning
confidence: 99%
“…As such, water flow in CNTs has been used to model the swelling of clay minerals [ 9 ], the much more complicated flow of (multiphase) oil-water mixtures through rock formations and water diffusing through cement, rocks and soil (e.g., through nanoporous zeolites) [ 10 ], with these results informing geological models of underground reservoirs. Furthermore, this is an excellent platform for studying water-surface interactions at the nanoscale, which can lead to insights for enhancing the effectiveness of several catalyst nanoparticles [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that confined water remains in the liquid state well below the freezing temperature of bulk water ( 273 ). It seems that the concentric water rings freeze at around 240 [ 11 ], although the central stratified water chain is shown to remain liquid at much lower temperatures ( 220 ) [ 52 ]. In any case, the actual freezing temperatures of these components depend on the CNT’s diameter and possibly the hydrogen isotope of water (i.e., heavy versus light water).…”
Section: Introductionmentioning
confidence: 99%